The Femoro‐Epiphyseal Acetabular Roof (FEAR) Index: A New Measurement Associated With Instability in Borderline Hip Dysplasia?. Issue 3 (March 2017) - Wyatt, Michael; Weidner, Jan; Pfluger, Dominik; Beck, Martin
Abstract: Background: The definition of osseous instability in radiographic borderline dysplastic hips is difficult. A reliable radiographic tool that aids decision‐making—specifically, a tool that might be associated with instability—therefore would be very helpful for this group of patients. Questions/purposes: (1) To compare a new radiographic measurement, which we call the Femoro‐Epiphyseal Acetabular Roof (FEAR) index, with the lateral center‐edge angle (LCEA) and acetabular index (AI), with respect to intra‐ and interobserver reliability; (2) to correlate AI, neck‐shaft angle, LCEA, iliocapsularis volume, femoral antetorsion, and FEAR index with the surgical treatment received in stable and unstable borderline dysplastic hips; and (3) to assess whether the FEAR index is associated clinical instability in borderline dysplastic hips. Methods: We defined and validated the FEAR index in 10 standardized radiographs of asymptomatic controls using two blinded independent observers. Interrater and intrarater coefficients were calculated, supplemented by Bland‐Altman plots. We compared its reliability with LCEA and AI. We performed a case‐control study using standardized radiographs of 39 surgically treated symptomatic borderline radiographically dysplastic hips and 20 age‐matched controls with asymptomatic hips (a 2:1 ratio), the latter were patients attending our institution for trauma unrelated to their hips but who had standardized pelvic radiographs between January 1, 2016 and March 1, 2016. Patient demographics were assessed using univariate Wilcoxon two‐sample tests. There was no difference in mean age (overall: 31.5 ± 11.8 years [95% CI, 27.7‐35.4 years]; stable borderline group: mean, 32.1± 13.3 years [95% CI, 25.5‐38.7 years]; unstable borderline group: mean, 31.1 ± 10.7 years [95% CI, 26.2‐35.9 years]; p = 0.96) among study groups. Treatment received was either a periacetabular osteotomy (if the hip was unstable) or, for patients with femoroacetabular impingement, either an open or arthroscopic femoroacetabular impingement procedure. The association of received treatment categories with the variables AI, neck‐shaft angle, LCEA, iliocapsularis volume, femoral antetorsion, and FEAR index were evaluated first using Wilcoxon two‐sample tests (two‐sided) followed by stepwise multiple logistic regression analysis to identify the potential associated variables in a combined setting. Sensitivity, specificity, and receiver operator curves were calculated. The primary endpoint was the association between the FEAR index and instability, which we defined as migration of the femoral head either already visible on conventional radiographs or recentering of the head on AP abduction views, a break of Shenton's line, or the appearance of a crescent‐shaped accumulation of gadolinium in the posteroinferior joint space at MR arthrography. Results: The FEAR index showed excellent intra‐ and interobserver reliability, superior to the AI and LCEA. The FEAR index was lower in the stable borderline group (mean, −2.1 ± 8.4; 95% CI, −6.3 to 2.0) compared with the unstable borderline group (mean, 13.3 ± 15.2; 95% CI, 6.2‐20.4) (p < 0.001) and had the highest association with treatment received. A FEAR index less than 5° had a 79% probability of correctly assigning hips as stable and unstable, respectively (sensitivity 78%; specificity 80%). Conclusions: A painful hip with a LCEA of 25° or less and FEAR index less than 5° is likely to be stable, and in such a situation, the diagnostic focus might more productively be directed toward femoroacetabular impingement as a potential cause of a patient's pain, rather than instability. Level of Evidence: Level III, diagnostic study.